Robust model for simulating sea surface current from RADARSAT - 1 SAR data - Maged Mahmoud Marghany, author; Mazlan Hashim, 1961-, author; Adil Mohd., author; Mohamed Maiys, author; Shattri Mansor, author; IEEE International Geoscience and Remote Sensing Symposium (2007: Barcelona, Spain) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL